Synthesis and Characterization of Chitosan-Nanosilver Microsphere by Ultrasonic Irradiation - Zhang, Hongyan; Yao, Baohui; Zai, Mengnan (Asian Journal of Chemistry, 2014)
Chitosan-nanosilver microspheres were synthesized by emulsion cross-linking method by ultrasonic irradiation. The microspheres were characterized by means of FTIR, XRD, SEM and DSC-TGA, respectively. FTIR showed that nanocomposites were embedded in microspheres. X-ray diffraction showed that chitosan was amorphous crystal and silver nanoparticles were face-centered cubic silver. Scanning electron microscopic evidenced that the morphology of samples all spherical with mean diameters 90 μ. TGA-DSC showed that chitosan molecules were changed, crystallization of chitosan was decreased, so the heat was low when the microspheres were decomposed.